2008
DOI: 10.1007/s00267-008-9071-0
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Off-Road Vehicles (ORVs) on Macrobenthic Assemblages on Sandy Beaches

Abstract: Sandy beaches are the prime sites for human recreation and underpin many coastal economies and developments. In many coastal areas worldwide, beach recreation relies on the use of off-road vehicles (ORVs) driven on the shore. Yet, the use of ORVs is not universally embraced due to social conflicts with other beach user groups and putative environmental consequences of vehicle traffic on sandy shores. Such ecological impacts of ORVs are, however, poorly understood for endobenthic invertebrates of the intertidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 44 publications
1
33
2
Order By: Relevance
“…Zones were defined through similarities in environmental characteristics, using group-average clustering, based on normalised Euclidean distance (Schlacher and Thompson 2007b). The cluster analyses included five environmental variables: (1) mean sediment grain size, (2) percent sediment moisture content, (3) elevation above low water, (4) slope and (5) the position of each sample relative to the effluent line (binary) (Schlacher et al 2008a). Broadly, our physically defined zones correspond, in general terms, to the biological zones defined by Dahl (1952), where the lower zone in this study is roughly congruent to the sublittoral fringe, the middle shore matches the midlittoral zone and the upper shore corresponds to Dahl's (1952) subterrestrial fringe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zones were defined through similarities in environmental characteristics, using group-average clustering, based on normalised Euclidean distance (Schlacher and Thompson 2007b). The cluster analyses included five environmental variables: (1) mean sediment grain size, (2) percent sediment moisture content, (3) elevation above low water, (4) slope and (5) the position of each sample relative to the effluent line (binary) (Schlacher et al 2008a). Broadly, our physically defined zones correspond, in general terms, to the biological zones defined by Dahl (1952), where the lower zone in this study is roughly congruent to the sublittoral fringe, the middle shore matches the midlittoral zone and the upper shore corresponds to Dahl's (1952) subterrestrial fringe.…”
Section: Discussionmentioning
confidence: 99%
“…1). We aimed to disperse sites equally along the length of the beaches, but their exact location in the spill area was dictated by logistical and operational constraints; reference sites were chosen based on previous sampling Thompson 2007a, 2008;Schlacher et al 2008a). All sites except Peregian beach (Per; Fig.…”
Section: Beaches Studiedmentioning
confidence: 99%
“…Those authors also found that ghost crab densities were higher in areas of low to moderate traffic, while individuals were smaller in heavily impacted areas, suggesting alterations of the population structure. Heavily trafficked beaches also had lower abundance, species richness, and diversity of intertidal macrobenthos, and strong changes in the community structure were driven by the low abundances of cirolanid isopods (Schlacher et al 2008). Direct crushing appeared to be the main cause of community change.…”
Section: Off-road Vehicle Trafficmentioning
confidence: 99%
“…Globally, many studies (e.g. McLachlan & Jaramillo 1995, Defeo & McLachlan 2005, Dugan et al 2011, Schlacher et al 2008) have demonstrated that the structure and nature of the habitat, fauna, and services offered by the supratidal and intertidal (= supralittoral and littoral) differ substantially (Fig. 3).…”
Section: Literature On Sand Beach Communitiesmentioning
confidence: 99%
“…Still, human recreational activities have been recognised to negatively affect beach fauna due to the intensive use of beaches (Schlacher and Thompson, 2012;Schlacher et al, 2011;Ugolini et al, 2008;Veloso et al, 2008) and to the impact of off-road vehicles (e.g. Schlacher et al, 2008a;Sheppard et al, 2009;Schlacher and Lucrezi, 2010;Walker and Schlacher, 2011).…”
Section: Introductionmentioning
confidence: 99%